KIPRAH BANK RAKYAT INDONESIA DALAM MENDUKUNG USAHA MIKRO KECIL MENENGAH SEKTOR PERIKANAN - Harsuko Riniwati (Jurnal Keuangan dan Perbankan, 2011)
Fisheries development faced several constraints: the ability to produce low compared to the available potential,product marketing and financing for the factors of production. These problems led the banking sector still tolook at the marginal of fisheries sector, especially small and medium micro enterprises. The purpose of thisstudy was to analyze: (1) feasibility study of freshwater fish culture, (2) parameters BRI management decisionmaking in lending to micro entrepreneurs, particularly freshwater fish farmers, (3) the role of BRI in increasingproduction of freshwater fish cultivation, (4) formulating a funding model that allowed fresh water fishfarmer accessible. The results showed that freshwater fisheries were generally feasible to be developed throughcredit of BRI. Credit model could be done in cooperation with institutions that allowed a guarantor of KUDMina, core plasma, consultants of SMEs, self partners, microfinance institution and marine and fisheriesdepartment.